Biochar-Mediated Control of Phytophthora Blight of Pepper Is Closely Related to the Improvement of the Rhizosphere Fungal Community - Wang, Guangfei; Ma, Yan; Chenia, Hafizah Yousuf; Govinden, Roshini; Luo, Jia; Ren, Gaidi (Frontiers in Microbiology, 2020)
Biochar is a new eco-material with the potential to control soil-borne diseases. This study explored the relationship between the rhizosphere fungal community and suppression of Phytophthora blight of pepper in the context of time after biochar application. A pot experiment was conducted and rhizosphere soils were sampled to determine the biochar-induced soil chemical properties , fungal community composition and abundance of biocontrol fungi. The biochar-enriched fungal strains were screened by the selective isolation method, and their control effects against Phytophthora blight of pepper were determined using a pot experiment. Biochar treatments effectively inhibited pathogen growth and controlled disease, with biochar applied immediately before planting (BC0) having greater effects than that applied 20 days before planting (BC20). Compared to the control, biochar-amended rhizosphere soils had a higher pH, available nutrient content, and fungal richness and diversity. Moreover, biochar treatments significantly increased the abundance of potential biocontrol fungi. The proliferation in BC0 was stronger as compared to that in BC20. Several strains, belonging to Aspergillus, Chaetomium, and Trichoderma, which were enriched by biochar amendment, demonstrated effective control of Phytophthora blight of pepper. Canonical correspondence and Pearson correlation analysis showed that high content of soil available nutrients in biochar treatments was favorable to the proliferation of beneficial fungi , which was negatively correlated with both the abundance of P. capsici and disease severity. In conclusion, biochar-mediated improvement in the fungal community suppressed the Phytophthora blight in pepper . The biochar application time had a great impact on the control effect, possibly due to the short-term proliferative effect of the biochar on biocontrol fungi.